Design, Optimization, and Characterization of Herbal Face Pack - Jain, Saloni (Asian Journal of Pharmaceutics (AJP), 2022)
The goal of this project is to develop and test a polyherbal face pack made of herbal substances for cosmetic purposes. Amla (Emblica officinalis), masoordaal (Lens culinaris), and rose petals were obtained from a local market and dried, powdered, then geometrically blended and analyzed for organoleptic and physico-chemical, general powder characteristics, and chemical assessment. The mixed dry powder has an acceptable flow property, making it ideal for use as a face pack. Four distinct compositions incorporating components such as Amla (E. officinalis), masoordaal (L. culinaris), and rose petals powder were developed with variable quantities and called F1 to F4. Different metrics such as organoleptic qualities, physicochemical parameters, and stability, as well as an irritancy test and microbiological load, were used to assess all of the created compositions. The powder’s particle size ranged from 23.3 to 26.9 m. F2 outperformed all other formulations in terms of physical metrics, skin irritation, and consistency even after stable storage conditions.